Multibeam bathymetry raw data (EM 120 echosounder entire dataset) of RV METEOR during cruise M70/1 - André Freiwald; Silvia Ceramicola; Alessandra Savini; Guiseppe Verdicchio; Paul Wintersteller (PANGAEA, 2021)
Multibeam bathymetry raw data using the ship extquotesingles own Kongsberg (Simrad) EM 120 multibeam echosounder was almost continuously recorded during RV METEOR cruise M70/1. Data were recorded on 23 days between 2006-09-24 and 2006-10-17. Data cover various areas in the Mediterranean Sea. The approximate average depth of the entire dataset is around 1900m. During data acquisition the Kongsberg EM 710 multibeam echosounder was occasionally running simultaneously during the survey. The data are archived at the Federal Maritime and Hydrographic Agency of Germany (Bundesamt für Seeschifffahrt und Hydrographie, BSH) and provided to PANGAEA database for data curation and publication. No ancillary sound velocity profiles (SVP) from the cruise are archived at the BSH, thus added to this dataset. However, data analysis of the raw data reveled that SVP has been changed on several occasions during the cruise. This publication is conducted within the efforts of the German Marine Research Alliance in the core area "Data management and Digitalization" (Deutsche Allianz Meeresforschung, DAM). Data are unprocessed and therefore may contain incorrect depth measurements (artifacts) without further processing. Data can be processed e.g. with the open source software package MB-System (Caress, D. W., and D. N. Chayes, MB-System: Mapping the Seafloor, http://www.mbari.org/products/research-software/mb-system/, 2021).